PELATIHAN PERCAKAPAN SEHARI-HARI BAHASA MANDARIN DI YAYASAN PANTI ASUHAN YATIM PIATU DAN DHUAFA MAKTABUL AITAM TANGERANG - Nurhayati Nurhayati; Dyas Mulyani Benazir (Jurnal Pengabdian Sosial, 2023)
ABSTRACT Chinese or also called Mandarin is one of the official languages used in meetings of members of the United Nations (UN) so that it shows its important position in the international world and is a language that is difficult to master because it is in addition to pictograph forms. In its development, Mandarin has been widely studied in various countries, one of which is in Indonesia, because Mandarin is the language of business communication. Mandarin is taught in schools, universities, course institutions and training both offline and online. Chinese language training is conducted to improve Chinese language skills, namely listening (listening), speaking, reading and writing Han characters. The training, which was conducted at the Maktabul Aitam Orphanage and Dhuafa Orphanage Foundation, targeted students who had never studied Mandarin before. So the first thing to teach is to recite the Chinese phonetic alphabet and carry out daily conversations. However, due to differences in the alphabet in how to read and also the tone or tonality so that students experience difficulty in pronouncing it. The solution given is to teach slowly and repeatedly, also demonstrated so that it is easy to pronounce and memorize. The method of implementing Community Service activities is educational in nature and trains students to communicate in Mandarin, especially daily conversations at the Maktabul Aitam Orphanage Foundation. The result of this activity is that students are taught daily conversations in Mandarin. Besides that, it also broadens students' horizons to learn foreign languages other than English as a provision for their future work. Keywords: Training, Conversation, and Mandarin Language